A sliding mode torque and position controller for an antagonistic SMA actuator. (September 2015) - Ianagui, André; Tannuri, Eduardo Aoun
Highlights: A nonlinear model of antagonistic wire shape memory alloy actuator is developed. Model parameters were optimized and validated with experiments. Sliding modes control law is derived from the model for position and torque control. A nonlinear state observer is developed in order to feedback unmeasured variables. Experimental results show good dynamic and tracking performance. Abstract: This paper presents position and torque control of an antagonistic setup for a shape memory alloy (SMA) rotary actuator using a sliding mode controller that takes into account the nonlinear behavior of SMA. The control scheme and model are based on the complete physics model of the system. An accurate model of the actuator is presented and validated by means of an experimental prototype. A nonlinear state observer is also developed in order to estimate temperature and phase state variables that are difficult to measure online due to the small dimensions of the actuator. Experimental results are then presented for different set-point functions. Tracking performance, frequency response and disturbance rejection are evaluated and the advantages of the proposed controller are then discussed.